Development Of Fuel Consumption Map Of A Myvi Engine Running On A Mixture Of RON 95 And RON 97 Gasoline - Aaron Ting, Zai Chiun (Universiti Sains Malaysia, 2018)
This paper aims to create a 3D fuel consumption map for a Myvi engine (Daihatsu K3-VE) running on a half mixture of RON 95 and RON 97 fuel. A burette is used as the measuring device for determining the amount of fuel consumed within a specified period of time. Before the experiment is started, the density of both fuels are determined using a measuring cylinder and an electronic digital weighing scale. The LHVs of both fuels are also determined before the experiment is carried out by using a bomb calorimeter. An engine fuel consumption map is constructed using two main data – engine speed and engine torque. It is usually done by fixing the torque of the engine and increasing the engine speed. This process is repeated with other values of torque. This means that a wide array of torque-speed combinations are needed to form the map. Because of the large amounts of data that must be collected in conventional engines, engineers are always looking for new methods of drawing more power with less fuel consumption besides manually setting the torque and speed by trial and error. One of the solutions to this problem is to create a generalization or a map whereby the desired output of an engine can be obtained simply after determining the input parameters and plugging them into the map. We are especially concerned with the change in fuel consumption in different situations governed mainly by using engine speed and torque as the input parameters. As compared to carrying out experiments to determine the desired output trend, creating the fuel consumption map can greatly reduce the amount of testing time as well as provide robust results.